2008
DOI: 10.1016/j.tpb.2007.11.010
|View full text |Cite
|
Sign up to set email alerts
|

On the evolution of epistasis III: The haploid case with mutation

Abstract: Whether interaction between genes is better represented by synergistic or antagonistic epistasis has been a focus of experimental research in bacterial population genetics. Our previous research on evolution of modifiers of epistasis in diploid systems has indicated that the strength of positive or negative epistasis should increase provided linkage disequilibrium is maintained. Here we study a modifier of epistasis in fitness between two loci in a haploid system. Epistasis is modified in the neighborhood of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Epistasis is then chosen to be homogenous among loci, being either positive or negative. With this framework it was shown that epistasis could largely influence the way populations would respond to selection (Kimura and Maruyama 1966;Charlesworth 1990;Kauffman 1993;Hansen and Wagner 2001;de Visser and Elena 2007), and some recent studies have shown how natural selection shapes epistasis (Liberman and Feldman 2005, 2006, 2008Desai et al 2007;Liberman et al 2007). However, all experimental data, to date, have found that both kinds of epistasis were present simultaneously (Elena and Lenski 1997;Sanjuan et al 2005;Jasnos and Korona 2007), and therefore such theories should be revisited to see how robust they are to the presence of both kinds of epistasis (Kouyos et al 2006(Kouyos et al , 2007.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Epistasis is then chosen to be homogenous among loci, being either positive or negative. With this framework it was shown that epistasis could largely influence the way populations would respond to selection (Kimura and Maruyama 1966;Charlesworth 1990;Kauffman 1993;Hansen and Wagner 2001;de Visser and Elena 2007), and some recent studies have shown how natural selection shapes epistasis (Liberman and Feldman 2005, 2006, 2008Desai et al 2007;Liberman et al 2007). However, all experimental data, to date, have found that both kinds of epistasis were present simultaneously (Elena and Lenski 1997;Sanjuan et al 2005;Jasnos and Korona 2007), and therefore such theories should be revisited to see how robust they are to the presence of both kinds of epistasis (Kouyos et al 2006(Kouyos et al , 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Evolution of the parameter Q depends on drift: Previous studies have analyzed the evolution of epistasis (Liberman and Feldman 2005, 2006, 2008Desai et al 2007;Liberman et al 2007). However, they focused on modifiers of epistasis acting on two loci or on modifiers of epistasis acting on many loci having mutations of similar effects on fitness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Once enough genes came to depend on this code, and cellular fitness increasingly depended on interdependent coordination of the action of many gene products, an evolutionary phase transition occurred that “froze” the genetic code [12, 13]. In parallel, increasingly complex fitness interactions among genes, called generally epistasis [14, 15], cooled the rate of gene sharing, changing the evolution of cells from a genetically communal to a more vertical mode of inheritance in a Statistical Tree of Life [16], in what Woese called the Darwinian Transition . Broadly consistent with this theory, it was found that complexity of gene interactions (the number of pairwise interactions a gene undertakes) constrains “informational” genes from transferring horizontally between cells relative to condition-dependent “operational” genes [17, 18] and increasing pairwise protein-protein interactions, as measured in yeast two-hybrid data, reduces substitution rates in proteins [19].…”
Section: Introductionmentioning
confidence: 99%